PERENCANAAN STRUKTUR ATAS RUANG BELAJAR PONDOK PESANTREN YATI/YAYASAN TARBIYAH ISLAMIYAH KAMANG MUDIK - Fajri Hamdani; Surya Eka Priana; Febrimen Herista (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The development of science must be accompanied by adequate facilities and infrastructure. Due to the increase in needs that must be met, the existing building is unable to accommodate learning activities. For this reason, it is necessary to improve facilities and infrastructure in the form of building additions, renovations or construction of new buildings, as is the case with the YATI Kamang Mudik Islamic Boarding School. With the increase in the number of students and the inadequate condition of the building, it is necessary to add a new building. This became the basis for the author to plan a new class building Ponpes YATI. From the results of the structural analysis, the structure repeating was obtained, the analysis that the author got was, the material used was steel fy = 420Mpa and fc '= 20.75Mpa. For the reinforcement of the floor plate, reinforcement is used for the direction x=Ø10-150, while the direction y=Ø1 0-150 is used. Ground floor column planning uses steel fy=240Mpa and fc'=24.9Mpa. With a size of 45cmX45cm. The planning of the 1st floor column uses steel fy=240Mpa and fc'=24.9Mpa. With a size of 40cmX40cm. The 2nd floor column planning uses fy=240Mpa and fc'=20.75Mpa steel. With a size of 35cm X 35cm. The planning of the 3rd floor column uses steel fy=240Mpa dan fc'=20.75Mpa. With a size of 35cmX35cm. While beam planning, for the main beam uses steel fy = 420Mpa and fc '= 20.75Mpa with a beam size of 50cmX30cm, for beam 2 and child beams using steel fy = 400Mpa and fc '= 20.75Mpa with a beam size of 2 45cmX25cm and a child beam of 35cmX25cm. Keywords: Building, Construction, Reinforcement, Steel Quality, Concrete Quality